International Entrepreneurship: Linking Entrepreneurial Motivation, Orientation and Network Relationship - Jurgita Sekliuckiene (Amfiteatru Economic Journal, 2015)
The paper analyses the importance of collaboration and networks in international entrepreneurship by distinguishing entrepreneurial small and medium firms (SMEs). SMEs, which characterized by fast internationalisation of their activity from the very beginning of the establishment despite limited resources, knowledge, international experience, are called born global. Such firms distinguish in entrepreneurial orientation, innovativeness, orientation towards niches, competitiveness and proactiveness towards international opportunities. The paper argues that the accelerator of entrepreneurial SMEs is their being in networks. Active interaction with customers, suppliers and external partners is inseparable from entrepreneurial orientation in pursuing for new possibilities in the market. The empirical data have been obtained from internationalized Lithuanian high-tech firms operating in the information technology sector. The paper presents motives, which determined the involvement of entrepreneurial SMEs into international markets, characteristics of entrepreneurial orientation as well as peculiarities of network relationship in Lithuania, a small Central and Eastern European country. The empirical evidence suggests that necessity to create national and international network relationships is the determinant success aspect of international expansion. The performed research extends the scope of international entrepreneurship research in emerging CEE countries.
Keywords: L14; L26; M13; M16; 330; international entrepreneurship; entrepreneurial orientation; entrepreneurial motivation; network; born global; information technology (IT) industry